Comparison of intracardiac echocardiography-guided versus conventionally performed cavotricuspidal isthmus ablation in patients with atrial flutter. (19th May 2022) - Janosi, K; Debreceni, D; Turcsan, M; Simor, T; Kupo, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cavotricuspidal isthmus (CTI) is the target of the catheterablation for patients with typical atrial flutters. Intracardiac echocardiography (ICE) allows safe, real-time visualization of the anatomical structures thus can help reduce the use of fluoroscopy and improve procedural outcomes. Purpose: We aimed to compare procedural and follow-up data of ICE vs. only-fluoroscopy guided procedures for CTI ablation in patients who underwent catheter ablation due to atrial flutter in our Institute. Methods: 154 consecutive patients were enrolled in our single-center retrospective study. In 70 patients, procedures were performed using fluoroscopy guidance only, while 84 patients underwent ICE-guided CTI ablation. Results: ICE-guidance significantly reduced fluoroscopy time (137 ± 60.2 s vs 918 ± 609.5 s; p<0.01), fluoroscopy dose (2.23 ± 1.44 mGy vs. 44.09 ± 25.23 mGy; p<0.01) and total procedure time (67.6 ± 25.8 min vs. 79.6 ± 23.9 min; p<0.01). Total ablation time (826 ± 445 s vs. 978.5 ± 676.8 s; p<0.01) and the time from the first to last ablation (25 ± 14 min vs. 43 ± 26.5 min; p<0.01) was also shorter in the ICE-guided group. Acute success rate was 100% and no major complications occurred in either group. Long-term success rate was 90.9% during the 2.13 ± 1.17 years follow-up period and did not differ between the groups (ICE-guided group: 94.1%, fluoroscopy-only group: 87.1%; p=0.14). Conclusion: ICE-guidance for CTI ablation can significantly reduce fluoroscopy exposure, procedure time and ablation time compared to the traditional, fluoroscopy-only approach.